THE ERROR OF STUDENTSâ€™ TRANSLATION FROM ENGLISH TO INDONESIAN OF SIXTH SEMESTER AT ENGLISH DEPARTMENT - Winda Walanda; Samsudin Hi. Adam; Susana R. Bahara (Jurnal Bilingual, 2022)
The purpose of this research was to find out the types of error from English into Indonesian text made by sixth semester students at English Department of Khairun University. This was descriptive qualitative research. This study involved 15 respondents who were taken by using purposive sampling technique. The result of this research showed that respondents made 4 types of errors in English into Indonesian translation text. The types of error were inversion, omission, deviation, and addition of meaning.Â  It can be concluded that the sixth semester students at English Department of Khairun University still made error when translating the English text.